Who controls the city?: A micro-historical case study of the spread of rioting across North London in August 2011. Issue 4 (3rd September 2019) - Ball, Roger; Stott, Clifford; Drury, John; Neville, Fergus; Reicher, Stephen; Choudhury, Sanjeedah
Abstract : In August 2011, over four days, rioting spread across several cities in England. Previous accounts of these riots have indicated the roles of police racism, class disadvantage, and spatial affordance. However, what remains unclear is how these structural factors interacted with crowd processes spatially over time to govern the precise patterns of spread. The present paper provides a micro-historical analysis of the patterns and sequences of collective behaviour as the 2011 riots spread across North London, drawing upon multiple data-sets (archive, interview, video, official report, news coverage). The analysis suggests that initial stages of escalation in the broader proliferation were the result of protagonists deliberately converging from areas of relative deprivation in order to create conflict, but that they did so as a meaningful social identity-based expression of power. We show how over time these motivations and patterns of collective action changed within the riot as a function of intergroup interactions and emergent affordances. On this basis, we provide support for the argument that political, social and economic geography were key determining factors involved in the pattern of spread of the 2011 riots. However, we also suggest that an adequate explanation must correspondingly take into account the interplay between social identity, the dynamics of intergroup interaction, and empowerment process that develop during riots themselves.